2018
DOI: 10.1101/282095
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting three-dimensional genome organization with chromatin states

Abstract: We introduce a computational model to simulate chromatin structure and dynamics. Starting from one-dimensional genomics and epigenomics data that are available for hundreds of cell types, this model enables de novo prediction of chromatin structures at five-kilo-base resolution. Simulated chromatin structures recapitulate known features of genome organization, including the formation of chromatin loops, topologically associating domains (TADs) and compartments, and are in quantitative agreement with chromosome… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 69 publications
7
50
0
Order By: Relevance
“…Methods that use information at the base pair level do not capture large scale continuous context and rather focus on window to window based predictions [8][9][10] . Methods that integrate a large genomic context do so by coarse segregation into genomic features [11][12][13] or polymer beads [14][15][16] , thus compromising on the base resolution. Here we present deepC, a deep neuronal network approach that can accurately predict Hi-C chromatin interactions from DNA sequence at megabase scale.…”
Section: Introductionmentioning
confidence: 99%
“…Methods that use information at the base pair level do not capture large scale continuous context and rather focus on window to window based predictions [8][9][10] . Methods that integrate a large genomic context do so by coarse segregation into genomic features [11][12][13] or polymer beads [14][15][16] , thus compromising on the base resolution. Here we present deepC, a deep neuronal network approach that can accurately predict Hi-C chromatin interactions from DNA sequence at megabase scale.…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear how well general noncoding impact methods will work on such variants, and they may be very far from genes, requiring a much larger total number of variants to be considered, with an accompanying rise in false positives. Advances in resolving three‐dimensional chromatin structure and how it varies (Kishi & Gotoh, ; Marti‐Renom et al, ; Qi & Zhang, ) hold long‐term hope for progress here.…”
Section: Discussionmentioning
confidence: 99%
“…What are the physicochemical interactions that stabilize the folded WT-like structures in cohesin-depleted cells? Numerous studies have demonstrated the importance of phase separation or compartmentalization in genome organization (63)(64)(65)(66)(67)(68)(69)(70)(71). Different regions of the chromatin could adopt distinct post-translational modifications on histone proteins.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…U b (r) is the harmonic bonding potential between neighboring beads with an equilibrium distance of 2.0σ and a spring constant of 1.0 /σ 2 . U sc (r) is a soft-core potential applied to all the non-bonded pairs to account for the excluded volume effect and to allow for chain crossing (53,68). It is equivalent to a capped off Lennard-Jones potential and only incurs a finite energetic cost for overlapping beads.…”
Section: Methodsmentioning
confidence: 99%